Standardized uptake value (SUV(max)) in (18)F-FDG PET/CT is correlated with the total number of main oncogenic anomalies in cancer patients - Haghighat Jahromi, Amin (Cancer Biol Ther, 2020)
Cancer diagnosis and therapy is quickly moving from the traditional histology-based approaches to genomic stratification, providing a huge opportunity for radiogenomics, associating imaging features with genomic data. Genome sequencing is time consuming, expensive and invasive whereas (18)F-FDG PET/CT is readily available, fast and noninvasive. The aim of this study was to determine the relationship between the maximum standardized uptake value (SUV(max)) and the frequency of 11 common oncogenic anomalies determined by specific common genomic alterations in tissue biopsies from patients with cancer. We retrospectively studied 102 consecutive untreated patients with gastrointestinal, lung, and breast cancer who underwent (18)F-FDG PET/CT imaging, shortly prior to molecular testing by a biopsy for genomic profiling that consisted of 11 common DNA alterations: (1) TP53, (2) DNA repair, (3) EGFR, (4) PI3K/AKT/MTOR (PAM) pathway including PTEN, PIK3CA, AKT, TSC, CCNB1, MTOR, FBXW2, and NF2, (5) MEK, (6) CYCLIN including CCND,CDK, CDKN, and RB, (7) WNT, (8) ALK, (9) MYC, (10) MET, and (11) FGF/FGFR. Higher SUV(max) was associated with the presence of TP53 and PAM genomic anomalies (p < .05), but not the other 9 gene groups (p > .05). More importantly, SUV(max) was positively correlated with total number of oncogenic anomalies (r = 0.27, p = .005). We propose higher SUV(max) as an indicator for total number of common oncogenic anomalies. This finding is a step forward in noninvasive stratification of cancer patients, in terms of the overall load of oncogenic anomalies, based on their SUV(max).